Budaya Kerja Bermutu Sebagai Standar Pelayanan Berkualitas - Rusdi, Rusdi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2023)
Service quality is a key element in organizational success, especially in the public and private service sectors. A quality work culture has an important role in establishing superior service standards. Therefore, this study aims to examine the relationship between quality work culture and high service standards in an effort to increase customer satisfaction and organizational performance. This study uses a quantitative approach to the survey method. The research sample involved employees of the Ministry of Religion regional offices in Central Kalimantan from various service-focused departments. Data was collected through a questionnaire assessing employee perceptions of work culture as service standards, as well as through available organizational performance data. Data analysis was performed using statistical regression techniques. The results of the study show that there is a significant relationship between quality work culture and high service quality. A work culture that is supported by values ​​such as integrity, professionalism, innovation, responsibility and exemplary tends to produce better service standards. These findings provide evidence that investing in the establishment of a quality work culture is the key to achieving quality service standards and supporting organizational success.